(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Autoimmune diseases are a heterogeneous group of pathologies characterised by impaired immunological tolerance and the production of autoantibodies directed against the body’s own tissues. Effective laboratory diagnostics plays a key role in early detection, monitoring and prediction of the course of these diseases. This review considers modern methods of laboratory diagnostics of autoimmune diseases, including serological, molecular-biological and functional tests, and evaluates their specificity and sensitivity in clinical practice [3,4,5].